Gambaran Sedentary Behaviour dan Indeks Massa Tubuh Mahasiswa Fakultas Kedokteran Universitas YARSI di Masa Pendidikan Tahun Pertama dan Kedua - Ahmad Rafi Faiq; Yenni Zulhamidah; Etty Widayanti (Majalah Sainstekes, 2018)
The prevalence of obesity and overweight increase in this recent decades, and leading to a decrease in quality of life and various health problems. Some studies found that the sedentary behavior is correlated with obesity and overweight. However, sedentary behavior is as an indicator of high fat mass in several studies. The aim of this study was to investigate the relationship between sedentary behavior and body mass index to medical students of YARSI University in first and second year of their education. The research design used correlation study with the Cross Sectional approach, and a questionnaire instrument to determine sedentary behaviour of respondents in daily activities. Body mass index was classified into four categories. Data was analyzed using Pearson Chi Square tests. The results of this study showed significantly between sedentary behavior in daily activities and the body mass index